(untitled) (Italian Journal of Public Health, 2011)
In this paper, an improved system that allows a simplified reporting of errors and near misses in wards, and permits operators to accurately manage all data recorded, is presented. IRGE (Incident Reporting with Gravity Effect) System is based on the use of a paper form for reporting accidents and near misses. The severity of an error can be evidenced through the choice of a color similar to the well-known method used in the emergency medicine triage, thus leading to the most evident and immediate understanding of the magnitude of error. In addition, the system is provided with a report form for its users to be compiled with the highest completeness of information. A dedicated software for the storage of records and data analysis has been created, which gives one the possibility of alerting key figures within the health facility promptly. The system allows us to store and share records among different care units and also among different hospitals, thus providing a basis for a national database. Moreover, through this system, it is possible to assess the “risk attitude” of the health facility monitored.